Is the Addition of a Polyol to Hyaluronic Acid a Significant Advance in the Treatment of Osteoarthritis? - Conrozier, Thierry (Current Rheumatology Reviews, 2018)
Viscosupplementation with intra-articular injections of hyaluronic acid is recommended as a second line treatment for knee OA, after failure of non-pharmacological modalities and usual pain killers. Nevertheless there are still controversies regarding clinical relevance of its effects. Research is looking for the best way to improve the performance of viscosupplementation in order to obtain a faster, longer-lasting and more pronounced effect. Antioxidants have been assessed in combination with hyaluronic acid because the injected hyaluronate is rapidly degraded by the reactive oxygen species, present in large amounts in the OA synovial fluid, limiting its residence time into the joint. Sorbitol and mannitol which have intrinsic free radical scavenger properties have been the most studied antioxidants. Sodium hyaluronate and polyols develop together a complex based on a dense network of hydrogen bonds which do not modify the visco-elsatic properties of hyaluronic acid. The oxygen free radicals neutralization by mannitol has been proven to delay the degradation of both linear and cross-linked HA in several in vitro models of oxidative stress. The antioxidant effect of these polyols may also play a role in accelerating onset of analgesia, as demonstrated in a double blind controlled trial comparing a mannitol-modified viscosupplement to regular hyaluronic acid. The addition of mannitol and sorbitol to hyaluronic acid does not alter the safety and local tolerability. In summary, adding a polyol to hyaluronic acid may improve the effects of viscosupplementation by reducing the rate of degradation of HA leading to a faster effect on pain relief without increasing the risk of adverse effect.
Keywords: viscosupplementation